Foreword - Vento, Giovanni; Lista, Gianluca (Acta Biomedica Atenei Parmensis, 2015)
This supplement of Acta Biomedica collects the Proceedings of the workshop “Dagli ELGA ai Late Preterm: quale approccio?”, held in Parma on 18-19 june 2015. The obstetrical assistance of pregnancies complicated by intrauterine growth restriction of foetus, the delivery room and NICU management of respiratory and cardiac failure, the modality of exogenous surfactant replacement by non invasive procedure (LISA) and the neurological outcome of very critical preterm babies, were the goals of our meeting with Italian and foreign speakers. With the hope that this supplement can arouse your interest and above all support you in everyday clinical practice, we wish you all good reading.